MERGER PERSEROAN TERBATAS DITINJAU DARI HUKUM PERSAINGAN USAHA - TS. Dwijayanti, Ayu Cindy; Tjukup, I Ketut (Kertha Semaya : Journal Ilmu Hukum, 2013)
This article named “Liability Company Merger In Terms Of Competition Law” has a purpose to know about the procedures of merger in a limited liability company and a limited liability company merger which is categorized a monopolistic practices and unfair business competition. The methods that used in this research is normative methods. The Merger is options strategy restructuring of business activities that can be done by a limited liability company. Implementation of the merger is a limited liability company must be in accordance with the procedures in force and there is no indication of competition and antitrust business practices are unhealthy.
Keywords: Business Competition, Mergers, A Limited Liability Company